THE STUDY OF SACRIFICE AND CUSTOMER SATISFACTION THAT INFLUENCE CUSTOMERS’ REPURCHASE INTENTION AT NOODLE RESTAURANT - Sugianto, Martin Julian; Wibisono, Yogi Yusuf (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
According to the Minister of Industry and the Central Statistics Agency, the food and beverage industry or business has contributed 1.2 quadrillion or 6.32% of Indonesia's total economic income in 2022. There are many food businesses spread across Indonesia, one of which is Restaurant X. The problem found was that there was a decrease in revenue at Restaurant X’s income starting from 2020 to 2023, causing difficulty in achieving targets every month. The purpose of this research is to identify and analyze the key factors that influence customer repurchase intentions at Restaurant X. The decrease in revenue occurred due to a decrease in the number of customers. Therefore, the purpose of this study is to determine the factors that can influence customer repurchase intentions at Restaurant X. In the research there are several variables, namely service quality, food quality, sacrifice, and customer satisfaction. Data collection was carried out using a questionnaire with a sampling technique in the form of convenience sampling. Data processing was carried out using the PLS-SEM (Partial Least Square-Structural Equation Model) method. This research succeeded in proving that service quality, food quality, and sacrifice influence customer satisfaction which then influences repurchase intention.